PENGUKURAN PERSEPSI TENAGA TEKNIS KEFARMASIAN DI KOTA DAN KABUPATEN SEMARANG TERHADAP APOTEK ONLINE - Fef Rukminingsih; Azifatul Ula; Dian Safitri (Jurnal Ilmiah Manuntung: Sains Farmasi Dan Kesehatan, 2022)
The development of online pharmacies in Indonesia will have an impact on the existence and role of Pharmaceutical Technicians. The number of pharmacies in Semarang City and Regency has reached almost 500 units. The number of Pharmaceutical Technicians who have practice permits in Semarang City is 477 people and in Semarang Regency is 115 people. Objective: This study aims to measure the perception of Pharmaceutical Technicians in Semarang City and Regency towards online pharmacies. Method: This research is a descriptive observational study using a cross sectional study design with using purposive sampling technique. The research data was obtained through a questionnaire in the form of a Likert scale which was distributed via google form in the Whatsapp group of Persatuan Ahli Farmasi Indonesia of Semarang City and Regency. Perceptions that are measured are drug guarantees, prices and consumer services. Pharmaceutical Technicians is said to have a positive perception of online pharmacies if the average score of the three parameters is in the range of 802.5 – 1284. Results: Respondents involved in this study were 321 respondents. Female respondents were 288 respondents (89.72%), 270 respondents (84.11%) aged less than 36 years and 177 respondents (55.14%) had Diploma III Pharmacy education. The drug guarantee parameter got a score of 1098, the drug price parameter got a score of 904 and the consumer service parameter got a score of 1035.5. The average score for the three parameters is 1012.5. Conclusion: Pharmaceutical Technicians in Semarang City and Regency have a positive perception toward online pharmacies.